PENGARUH LITERASI KEUANGAN DAN GAYA HIDUP TERHADAP PERILAKU KONSUMTIF PENGGUNA SHOPEE PAYLATER PADA GENERASI Z (STUDI KASUS PADA MAHASISWA FEBI IAIN SYEKH NURJATI CIREBON)) - Khaerunisa, Risma; Fanther, Refaldo; Sukardi, Didi (Universitas YPPI Rembang, 2024)
The aim of this research is to determine: 1) the influence of financial literacy on the consumptive behavior of Shopee paylater users. 2) the influence of lifestyle on the consumptive behavior of Shopee paylater users. 3) the influence of financial literacy and lifestyle on the consumer behavior of Shopee paylater users. This research uses quantitative research methods with a survey approach and uses primary data sources through questionnaires. The sampling technique used purposive sampling with a total of 97 respondents obtained using the Slovin formula. Data were collected using a questionnaire via a Google form which was distributed to respondents online. Data were analyzed using the SPSS 23.0 program. which analyzes research instrument tests, classical assumption tests, multiple linear regression analysis tests, and hypothesis tests. The findings from this research show that: 1) there is a negative and significant influence between financial literacy and the consumptive behavior of Shopee paylater users. 2) there is a positive and significant influence of lifestyle on the consumer behavior of Shopee paylater users. 3) there is a positive and significant influence of financial literacy and lifestyle together or simultaneously on the consumptive behavior of Shopee paylater users.